ENU‐induced mutant allele of Dnah1, ferf1, causes abnormal sperm behavior and fertilization failure in mice. Issue 4 (8th February 2019) - Hu, Jianjun; Lessard, Carl; Longstaff, Charles; O'Brien, Marilyn; Palmer, Kristina; Reinholdt, Laura; Eppig, John; Schimenti, John; Handel, Mary Ann
Abstract: Given attention to both contraception and treatment of infertility, there is a need to identify genes and sequence variants required for mammalian fertility. Recent unbiased mutagenesis strategies have expanded horizons of genetic control of reproduction. Here we show that male mice homozygous for the ethyl‐nitroso‐urea‐induced ferf1 (fertilization failure 1) mutation are infertile, producing apparently normal sperm that does not fertilize oocytes in standard fertilization in vitro fertilization assays. The ferf1 mutation is a single‐base change in the Dnah1 gene, encoding an axoneme‐associated dynein heavy chain, and previously associated with male infertility in both mice and humans. This missense mutation causes a single‐amino‐acid change in the DNAH1 protein in ferf1 mutant mice that leads to abnormal sperm clumping, aberrant sperm motility, and the inability of sperm to penetrate the oocyte's zona pellucida; however, the ferf1 mutant sperm is competent to fertilize zona‐free oocytes. Taken together, the various mutations affecting the DNAH1 protein in both mouse and human produce a diversity of phenotypes with both subtle and considerable differences. Thus, future identification of the interacting partners of DNAH1 might lead to understanding its unique function among the sperm dyneins. Abstract : Male mice homozygous for the ethyl‐nitroso‐urea‐induced ferf1 (fertilization failure 1) mutation are infertile, producing apparently normal sperm that do not fertilize oocytes in standard fertilization in vitro fertilization assays. The ferf1 mutation is a single‐base change in the Dnah1 gene, encoding an axoneme‐associated dynein heavy chain. This mutation causes a single‐amino‐acid change in the DNAH1 protein in ferf1 mutant mice that leads to abnormal sperm clumping, aberrant sperm motility, and the inability of sperm to penetrate the oocyte's zona pellucida.